Investigation of the Effect of 8-Week Reformer Pilates Exercise on Flexibility, Heart Rate and Glucose Levels in Sedentary Women - Suna, Gürhan; Işildak, Kenan (Asian Journal of Education and Training, 2020)
The aim of this study is to investigate the effects of reformer pilates exercises on flexibility, heart rate and glucose levels of sedentary women for 8 weeks. 30 sedentary women between 30-36 years old were joined to the study. Participated in the research sedentary women’ ages’ mean was 32,20±1,78 year, lenghts’ mean was 166,76±3,93 cm. It is announced to the participants that personal information and findings obtained during and after the research will be kept strictly confidential and also “Informed Voluntary Consent Form” was filled up. Reformer pilates exercise was performed regularly for 8 weeks, %40-60 loading intensity, 3 days a week, 60 minutes per day. Measurements were obtained as pre-test and post-test. SPSS programme was used. “Paired t test” was used to determine the difference before and after exercise. The results were evaluated at p<0,05 significance level. The comparison of body weight, resting-maximum heart rate, flexibility and glucose 1. day and 8. week post- exercise measurements were statistically significant (p<0,05). But there were no significant different in glucose 1. day and 8. week pre- exercise measurements (p>0,05). As a result of our study based on the data obtained, it was determined that regular reformer pilates exercises accelerated weight loss on sedentary women. In addition, it had positive effects on flexibility, heart rate and glucose measurements.